2004
DOI: 10.2135/cropsci2004.4430
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Trait Relationships in Switchgrass

Abstract: chromosome numbers ranging from 2n ϭ 2x ϭ 18 to 2n ϭ 12x ϭ 108 (Nielson, 1944;McMillan and Weiler, Greater knowledge of the magnitude of genetic variability for bio- Henry and Taylor, 1989). Switchgrass is classified mass yield and yield components in switchgrass, Panicum virgatum L., and relationships among the biomass yield component traits would into upland and lowland ecotypes based on morphology facilitate the breeding improvement of the species. Accordingly, we and habitat preference (Porter, 1966). All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
72
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 17 publications
13
72
2
1
Order By: Relevance
“…Boe & Lee (2007) reported h 2 n estimates of 0.60 and 0.62 from variance component methods for biomass yield for the upland ecotype varieties of switchgrass Sunburst and Summer, respectively. Das et al (2004) reported significant variability for biomass yield and several yield components in switchgrass but did not report heritability estimates of these traits.…”
Section: Introductionmentioning
confidence: 95%
“…Boe & Lee (2007) reported h 2 n estimates of 0.60 and 0.62 from variance component methods for biomass yield for the upland ecotype varieties of switchgrass Sunburst and Summer, respectively. Das et al (2004) reported significant variability for biomass yield and several yield components in switchgrass but did not report heritability estimates of these traits.…”
Section: Introductionmentioning
confidence: 95%
“…These ecotypes possess large genotypic, phenotypic, and physiological differences between them [13][14][15][16][17][18]. Lowland cultivars are generally tall, thick-stemmed, later flowering, adapted to wetter conditions, and have higher biomass yield potential, compared to the upland ecotypes [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented the variability that exists within available switchgrass populations with respect to important agronomic traits, such as tillering, digestibility and biomass production (Redfearn et al, 1997b;Das et al, 2004;Smart et al, 2004). Although, these studies have documented the potential for germplasm improvement in this important forage and biofuel crop there is still limited information on the anatomical, biochemical and physiological processes affecting these attributes.…”
Section: Introductionmentioning
confidence: 99%